Comprehensive analysis on aging behavior and safety performance of LiNixCoyMnzO2/graphite batteries after slight over-discharge cycle. (5th May 2023) - Li, Lun; Zhou, Xiaodong; Ju, Xiaoyu; Zhou, Zhizuan; Wang, Boxuan; Cao, Bei; Yang, Lizhong
Highlight: The thermal stability and thermal runaway criticality of the batteries after over-discharge cycle are studied. The over-discharge voltage plays a more important role than the number of cycles. Over-discharge cycle can deteriorate the battery safety performance and increase the risk of battery thermal runaway. The maximum safe storage temperature are calculated under different heat dissipation conditions. The dissolution of Cu initiated when over-discharged to 0.5–0.0 V. Abstract: Over-discharge is one of the common abuse conditions for lithium-ion batteries (LIBs), while the safety hazard of over-discharged cell is still unclear. In this work, the aging behavior and safety performance of commercial Li(Ni0.5 Co0.2 Mn0.3 )O2 /graphite LIBs under 1.5, 1.0, 0.5, and 0.0 V over-discharge cycles are investigated. The cells experience capacity decay and structural damage during over-discharge cycle. Compare to the normal cycled cells, the increased impedance after over-discharge cycle leads to more heat generation during operating, which further accelerates the inconsistency of LIB module. Moreover, the thermal runaway behavior of the over-discharged cell was studied using Extended Volume Accelerating Rate Calorimeter. The kinetics of self-heating reaction is obtained, and the criticality of thermal runaway under different heat dissipation conditions was analyzed based on Semenov model. The thermal stability and maximum safe storage temperature of the LIB were decreased after over-discharge cycle, especially for the cell over-discharged to 0.0 V. Based on the electrochemical impedance spectroscopy, the loss of lithium inventory relate to the growth of solid electrolyte interphase (SEI) film is found to be the primary aging contribution. Moreover, the post-mortem test implied the dissolution of Cu initiated when over-discharged to 0.5–0.0 V.